BATAN PERSONAL DOSE EQUIVALENT Hp (10) AND Hp (3) INTERCOMPARISON RESULTS AT 2018 & 2019 - Assef Firnando Firmansyah; Okky Agassy Firmansyah; Rizka Sarah Melinda (Badan Standardisasi Nasional, 2021)
One of the methods to ensure the quality of a laboratory is participating in an intercomparison activity. For the dosimetry laboratory network in Indonesia, the intercomparison activity is managed by the Secondary Standard Dosimetry Laboratory (SSDL) Jakarta. This paper describes the intercomparison among processing laboratory for personal dose equivalent Hp(10) and Hp(3) using thermoluminescent dosimeter (TLD)/films in 2018 & 2019. The SSDL Jakarta irradiated packages of participant's TLDs/films with Cs-137 and X-rays at a specific equivalent dose. The irradiated dosimeters were sent back to the participants by mail, and then the result was sent to the SSDL Jakarta for evaluation. The evaluation was carried out using the trumpet curve under the International Atomic Energy Agency (IAEA) publication. The results obtained for the 2018 intercomparison show the success rates of 98%, and 2% were outside the acceptable range, whereas for the 2019 Intercomparison, the success rates were 96% and 4% outside the acceptable range. The potential failure of reading the dose value was in the film dosimeter/badge. For those recent two years of intercomparison activities, the success rate was more than 95%. This result of the intercomparison activity showed the excellent quality of the personal dose equivalent Hp(10) and Hp(3) measurement in Indonesia.